#### Answer

-$\frac{15}{13y}$

#### Work Step by Step

-$\frac{15}{26y}$ - $\frac{15}{26y}$
= $\frac{-15 -15}{26y}$
=$\frac{-30}{26y}$
=-$\frac{2\times15}{2\times13y}$
=-$\frac{15}{13y}$

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

-$\frac{15}{13y}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.